Creation of curricular material in different Educational Systems - García Encabo, Carmelo (Avances en Supervisión Educativa, 2007)
Curricular material is a concept that has undergone a development similar to the one of several Social Science concepts which, by assuming different elements, turned out to be multi-meaning expressions. Throughout the last decades, curricular materials have been an excellent reference to trace the evolution of the Spanish Educational System in the last years and reflect on the relationship between the different theoretical proposals -supported by educational regulations- and the real facts as occurred at schools.